Phytochemical Screening and Antioxidant Activities of White and Red Wines from Different Varieties and Wine Regions in Romania - Ovidiu Tița; Petronela Anca Onache; Elisabeta-Irina Geana; Corina Teodora Ciucure; Dorin Ioan Sumedrea; Alina Florea (Antioxidants)
The characteristics of the variety from which the wine is made, the geographical area of production, the year of production, and the technology of winemaking are the parameters with the most influence on the total content of polyphenols, the polyphenolic profile, and the antioxidant activity of wine. For this reason, a polyphenolic screen can help establish the authenticity of wines. For this study, 50 samples of white and red wine from different wine areas were collected. For these samples, a qualitative and quantitative analysis was carried out on the polyphenolic profile. The polyphenolic profiles of the studied wines were determined using UHPLC-ESI-MS/MS (mass spectrometry with tandem ionization with high-performance liquid chromatography). Among the non-flavonoid acids, gallic acids, p-coumarnic, and syringic acids in red wines showed higher concentrations in all samples, while resveratrol was present in concentrations from 0.605 to 12.38 mg/L in red wines, and white wines ranged from 0.07 to 0.35 mg/L. For flavonoids, -catechin (0.187 m/L–130.98 mg/L in red wines and 0.04–4.45 mg/L) and (-)-epi-catechin showed the highest concentrations, reaching up to 29.78 mg/L in red wines.